The Aesthetic Unconscious - Rancière, Jacques 1940- (Cambridge Polity, 2010)
This book is not concerned with the use of Freudian concepts for the interpretation of literary and artistic works. Rather, it is concerned with why this interpretation plays such an important role in demonstrating the contemporary relevance of psychoanalytic concepts. In order for Freud to use the Oedipus complex as a means for the interpretation of texts, it was necessary first of all for a particular notion of Oedipus, belonging to the Romantic reinvention of Greek antiquity.
Keywords: 21st Century (2001-2100); Philosophy; Consciousness; Esthetics; France